(untitled) (Palimpsesto, 2023)
This work reconstructs the links that the Revolutionary Armed Forces (1970-1973) established with groups of activists in the Gran La Plata party. Our objective is to problematize the way in which the organization conceived its links with broader sectors of the social movement and provide an overview of its links with student groups at the university and secondary levels and sectors of neighborhood militancy. In this way, we intend to contribute to knowledge about the processes of social activation, politicization and radicalization of the early seventies, particularly in relation to the confluences and divergences between social protest and revolutionary politics. To do this, we resort to a qualitative strategy based on the triangulation and analysis of documentary sources and oral interviews with protagonists.